A simple method to back-project isocenter dose of radiotherapy treatments using EPID transit dosimetry - Thiago Bernardino da Silveira; Bianca de Quadros Cerbaro; Luiz Antônio Ribeiro da Rosa (Brazilian Journal of Radiation Sciences, 2017)
The aim of this work was to implement a simple algorithm to evaluate isocenter dose in a phantom using the back-projected transmitted dose acquired using an Electronic Portal Imaging Device (EPID) available in a Varian Trilogy accelerator with two nominal 6 and 10 MV photon beams. This algorithm was developed in MATLAB language, to calibrate EPID measured dose in absolute dose, using a deconvolution process, and to incorporate all scattering and attenuation contributions due to photon interactions with phantom. Modeling process was simplified by using empirical curve adjustments to describe the contribution of scattering and attenuation effects. The implemented algorithm and method were validated employing 19 patient treatment plans with 104 clinical irradiation fields projected on the phantom used. Results for EPID absolute dose calibration by deconvolution have showed percent deviations lower than 1%. Final method validation presented average percent deviations between isocenter doses calculated by back-projection and isocenter doses determined with ionization chamber of 1,86% (SD of 1,00%) and -0,94% (SD of 0,61%) for 6 and 10 MV, respectively. Normalized field by field analysis showed deviations smaller than 2% for 89% of all data for 6 MV beams and 94% for 10 MV beams. It was concluded that the proposed algorithm possesses sufficient accuracy to be used for in vivo dosimetry, being sensitive to detect dose delivery errors bigger than 3-4% for conformal and intensity modulated radiation therapy techniques.